The Bondwoman's Narrative - Crafts, Hannah; Gates, Henry Louis (New York : Warner Books, 2002)
When her master is betrothed to a woman who conceals a tragic secret, Hannah Crafts, a young slave on a wealthy North Carolina plantation, runs away in a bid for her freedom up North. Pursued by slave hunters, imprisoned by a mysterious and cruel captor, held by sympathetic strangers, and forced to serve a demanding new mistress, she finally makes her way to freedom in New Jersey. An unprecedented historical and literary event, this tale written in the 1850's is the only known novel by a female African American slave, and quite possibly the first novel written by a black woman anywhere. A work recently uncovered by renowned scholar, Henry Louis Gates, Jr., it is a stirring, page-turning story of "passing" and the adventures of a young slave as she makes her way to freedom. When Professor Gates saw that modest listing in an auction catalogue for African American artifacts, he immediately knew he could be on the verge of a major discovery. After exhaustively researching the hand-written manuscript's authenticity, he found that his instincts were right. He had purchased a genuine autobiographical novel by a female slave who called herself- and her story's main character- Hannah Crafts. Presented here unaltered and under its author's original title, The Bondswoman's Narrative tells of a self-educated young house slave who knows her life is limited by the brutalities of her society, but never suspects that the freedom of her plantation's beautiful new mistress is also at risk...or that a devastating secret will force them both to flee from slave hunters with another powerful, determined enemy at their heels. Together with Professor Gates's brilliant introduction- which includes the story of his search for the real Hannah Crafts, the biographical facts that laid the groundwork for her novel, and a fascinating look at other slave narratives of the time- The Bondwoman's Narrative offers a unique and unforgettable reading experience. In it, a voice that has never been heard rings out, and an undiscovered story at the heart of the American experience is finally told.
Bondwoman's narrative -- Textual annotations: Appendices: Authentication report / Dr. Joe Nickell -- Testimony of Jane Johnson, version 1 -- Testimony of Jane Johnson, version 2 / Bryan C. Sinche -- John Hill Wheeler's Library catalogue.
Includes bibliographical references (p. 333-336).
Keywords: African American women -- Fiction; Plantation owners' spouses -- Fiction; Women -- North Carolina -- Fiction; Women -- Virginia -- Fiction; Multiracial people -- Fiction; Passing (Identity) -- Fiction; Plantation life -- Fiction; North Carolina -- Fiction; Fugitive slaves -- Fiction; Enslaved women -- Fiction; Virginia -- Fiction; Autobiographical fiction